Environmental risk management associated with the development one of oil fields in southwestern Iran using AHP and FMEA methods - Mahboobeh Cheraghi; Abdolreza Karbassi; Seyed Masoud Monavari; Akbar Baghvand (Anthropogenic Pollution)
Nowadays risk management is intended to be a solution in project management to deal with the risks and events that may occur in an industrial project. The risk management is a process that is able to identify, analyze risks and determine strategies to reduce the effects of that. Also, most managers are challenged, especially when they are supposed to choose between multiple solutions to a problem. In this project we have tried to use the FMEA and AHP techniques to evaluate the environmental risk posed by Ahvaz oil field development as well. List of aspects and environmental impacts of completed construction and operation phases and the scoring were based on the criteria mentioned methods. The level of risks were at three levels: low, medium and high, respectively. For the construction phase from all 35 rated risks 5 were high-level, 19 were medium-level, and 11 showed a low level of risk. Operation phase from all 29 risks 4 were high-level risk, 15 were medium risk and 10 were low-level. In the end, strategies for reducing environmental pollutants in construction, operation and management phase and in the framework of manpower, vehicles, materials and operations are provided.